1997
DOI: 10.1007/s002709900143
|View full text |Cite
|
Sign up to set email alerts
|

Non-marfan idiopathic medionecrosis (cystic medial necrosis) presenting with multiple visceral artery aneurysms and diffuse connective tissue fragility: Two brothers

Abstract: Two brothers with multiple visceral artery aneurysms or dilatations and diffuse connective tissue fragility who did not have clinical features of Marfan syndrome are reported. One presented with retroperitoneal hemorrhage during angiography, and idiopathic medionecrosis was proved by resection of the aneurysms. These cases belong to the heterogeneous group of Marfan syndrome. The angiographical features (multiple dilation of visceral arteries) suggests fragility of connective tissue and is predictive of hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…23 Reported surgical procedures for isolated EIAAs consist of stent grafting (36%), graft replacement (27%), bypass procedures (18%), and common iliac artery ligation (9%). 2,5,22 Stent grafting is novel, but still presents challenges. Caronno et al stated that its usefulness lay in the fact that it was not associated with primary technical failure, major complication, or perioperative mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Reported surgical procedures for isolated EIAAs consist of stent grafting (36%), graft replacement (27%), bypass procedures (18%), and common iliac artery ligation (9%). 2,5,22 Stent grafting is novel, but still presents challenges. Caronno et al stated that its usefulness lay in the fact that it was not associated with primary technical failure, major complication, or perioperative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,22 Crivello et al suggested that iliac artery aneurysms caused by CMN present signifi cantly higher operative risks because of their vascular fragility. 5 Although the pathological fi ndings revealed CMN in our patient, fortunately arterial vulnerability was not recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone excess can be associated with excess mucopolysaccharide deposition characteristic by both CMN and extensive myxomatous degeneration, which even invading all four cardiac valves [44]. CMN can be the underlying cause of heterogeneous Marfan's syndrome [48,49], aneurysm of the circumflex coronary artery [50], spontaneous dissection of the internal thoracic artery [49], aortic valve commissure tear [51], spontaneous dissection of massive bilateral sinus of Valsalva aneurysms [52], pulmonary artery aneurysm [53], and carotid artery aneurysm [20]. Aortic root aneurysm due to donor CMN after heart-lung transplantation was also noted [54].…”
Section: Fig 5 -Histology Of the Ascending Aorta Of A 59-year-old Mamentioning
confidence: 99%
“…9 In fact, although cystic medial necrosis is associated with known collagen-vascular disorders, such as Marfan syndrome and Ehlers-Danlos syndrome, it can manifest as a separate entity. 10 Other causes for this patient's aneurysms are unlikely. For example, infection can lead to formation of a mycotic aneurysm.…”
Section: Discussionmentioning
confidence: 88%